Binding and neutralizing abilities of antibodies towards SARS-CoV-2 S2 domain - Xingsu Gao; Linlin Fan; Binyang Zheng; Haoze Li; Jiwei Wang; Li Zhang; Jingxin Li; Fengcai Zhu (Taylor & Francis Group, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) variants have been reported to be resistant to several neutralizing antibodies (NAbs) targeting Receptor Binding Domain (RBD) and N Terminal Domain (NTD) of spike (S) protein and thus inducing immune escape. However, fewer studies were carried out to investigate the neutralizing ability of S2-specific antibodies. In this research, 10 monoclonal antibodies (mAbs) targeting SARS-CoV-2 S2 subunit were generated from Coronavirus Disease 2019 (COVID-19) convalescent patients by phage display technology and molecular cloning technology. The binding activity of these S2-mAbs toward SARS-CoV-2 S, SARS-CoV-2 S2, SARS-CoV-2 RBD, SARS-CoV-2 NTD, severe acute respiratory syndrome coronavirus (SARS-CoV) S, SARS-CoV S2 and Middle East Respiratory Syndrome Coronavirus (MERS-CoV) S proteins were evaluated by enzyme-linked immunosorbent assay (ELISA). Their neutralizing potency toward SARS-CoV-2 wild-type (WT), B.1.1.7, B.1.351, P.1, B.1.617.2, B.1.1.1 and B.1.621 variants were determined by pseudo-virus-based neutralization assay. Results showed that S2E7-mAb had cross-activity to S or S2 proteins of SARS-CoV-2, SARS-CoV and MERS-CoV, while with limited neutralizing activity to pseudo-viruses of SARS-CoV-2 WT and variants. It is undeniable that the binding and neutralizing activities of the S2-targeting mAbs are significantly weaker than the previously reported antibodies targeting RBD and NTD, but our study may provide some evidences for understanding immune protection and identifying targets for vaccine design based on the conserved S2 subunit.